The Effectiveness of Using Augmented Reality Prehistoric Human Material Based on Unity 3D on the Quality of Learning Outcomes of Students in the History Education Study Program University of Flores - Samingan; Anita; Yosef Dentis (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
In today's digital era, technology has become an integral part of life, including in education. One of the increasingly popular technologies is Augmented Reality (AR), a technology that allows the integration of the real world with digital elements in one display. AR offers an interactive and immersive experience that can be used in education. The use of AR as a learning medium is expected to help students of the History Education Study Program to improve the quality of learning outcomes. The development of AR based on unity 3D is the right choice for history learning. This study uses a quantitative research method of quasi-experimental design with a pretest-posttest control group. The experimental class had an increase in the average value of the pretest and posttest of 12.13. While the control class had an increase in the average value of the pretest and posttest of 4.85. So there is a significant difference in the difference in the increase between the experimental and control classes of 8.02. For the first t-test by conducting a test on the posttest in the experimental class with the control class, the Sig. (2-tailed) value was obtained at 0.018 <0.05. So, it can be concluded that there is a significant difference between the learning outcomes of students in the experimental class and the control class. Then the second test-2 by comparing the pretest and posttest of the experimental class obtained a sig value (2-tailed) of 0.00 <0.005, so it can be concluded that there is a difference in student learning outcomes for the pretest and posttest in the experimental class. Thus, the effectiveness of using Augmented Reality on prehistoric human material based on unity 3D on the quality of learning outcomes of students in the History Education Study Program.